Breakup and coalescence of drops during transition from dripping to jetting in a Newtonian fluid. (March 2019) - Viswanathan, H.
Highlights: Axi-symmetric numerical simulations for predicting dripping to jetting transitions for a Newtonian fluid using the VOF model. Model results agree well with previously published experimental results and correlations for periodic dripping, dripping faucet and jet breakup lengths. New modes of satellite formation and merging with primary drops during chaotic dripping are identified. Prediction of coalescence of primary drops downstream during jetting. Abstract: We present numerical simulations of dripping to jetting transitions that occur during the flow of a Newtonian liquid. An axi-symmetric, Volume of Fluid (VOF) model along with Continuum Surface Force (CSF) representation is developed to capture various regimes of drop formation. By numerically studying different nozzle diameters subjected to various flow rates, we examine the critical conditions under which the dripping to jetting transition takes place. At every stage of dripping and jetting, we assess the accuracy of the present simulations through a number of comparisons with previously published experimental data and empirical correlation and find reasonable agreements. Our numerical simulations show different responses that characterize the dripping and the dripping faucet regimes leading to chaotic dripping patterns. Within the chaotic regime, we identify four unique modes of satellite formation and their merging patterns which have not been reported earlier. Finally, we observe that as soon as the flow rate approaches a threshold the jetting regime begins where, subsequent disintegration of drops and coalescence patterns are observed downstream. Detailed flow patterns, pressure distributions and drop shapes are provided for various dimensionless numbers alongside the spatial-temporal resolutions of both jetting and coalescence of primary drops. Of the many complex dynamics that influence the primary droplet coalescence, we find that the oscillatory motion of drops during their travel downstream, which is dampened normally due to viscous effects, can be influential and can aid both coalescence and breakup of droplets.